PERANCANGAN BOOKLET MEDIA KOMUNIKASI TUNA RUNGU DI SEKOLAH LUAR BIASA (SLB) YPAC SUMBAR - VICKY HARDIEN SARI, Drs. Syafwan, M.Si., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
In West Sumatra many schools are extraordinary or inclusive and students in schools have different types of barriers among them deaf. Hearing impairment is a hearing impairment, in part or in whole that has a complex impact on his life. When viewed physically look like normal normal person, but when invited to communicate then seen that they have hearing loss.Deaf people have obstacles in hearing and are often constrained in conveying and receiving information in communicating. In addition, the number of children with hearing impairment is increasing in schools but the communication media for deaf children is still lacking (minimally) provided by schools. Especially in the school YPAC West Sumatra.Therefore, to help communicate with children with hearing impairment required tools or media in communication facilities, such as written media, print media, electronic media and using sign language in accordance with the mandate of Law no. 8 of 2016 article 24 on Persons with Disabilities.Keywords: Deaf, Booklet, YPAC West Sumatera.